Penyuluhan Tanda Bahaya Kehamilan Trimester I di Dusun Uraur Nuduasiwa Kecamatan Kairatu Kabupaten Seram Bagian Barat Provinsi Maluku 2021 - Asih Dwi Astuti; Zubaeda; Dewi Susanti; Windatania Mayasari (Future Science, 2022)
One of the causes of the still high maternal mortality rate is the delay in assisting maternal emergency cases. The delay occurred because of the mother's lack of knowledge of the danger signs of pregnancy. Danger signs of pregnancy can occur in the first trimester, second trimester and third trimester. The purpose of community service is to increase understanding and increase knowledge about danger signs of pregnancy in the first trimester. The method used is to provide counseling on danger signs of pregnancy in the first trimester. The target for this activity is all pregnant women in the first trimester. Respondents in this activity were 20 people in Uraur Nuduasiwa Hamlet, Kairatu District, West Seram Regency, Maluku Province. Community Service is carried out in July 2021. Submission of Information through lecture and question and answer methods. An overview of the respondents' knowledge in this activity can be seen when conducting questions and answers about the danger signs of pregnancy in the first trimester. The increase in knowledge can be seen from the pre-test results of 5 people (25%) in the good category, after counseling there was an increase in knowledge of 90%. The conclusion obtained is that there is an increase in knowledge of the danger signs of pregnancy in the first trimester in Uraur Nuduasiwa Hamlet, Kairatu District, West Seram Regency, Maluku Province.